Influence of the A3669G Glucocorticoid Receptor Gene Polymorphism on the Metabolic Profile of Pediatric Patients with Congenital Adrenal Hyperplasia - Ricardo P. P. Moreira; Larissa G. Gomes; Guiomar Madureira; Berenice B. Mendonca; Tânia A. S. S. Bachega (International Journal of Endocrinology)
Background. Pediatric CAH patients have an increased risk of cardiovascular disease, and it remains unknown if genetic predisposition is a contributing factor. Glucocorticoid receptor gene (NR3C1) polymorphisms are associated with an adverse metabolic profile. Our aim was to analyze the association between the NR3C1 polymorphisms and the metabolic profile of pediatric CAH patients. Methods. Forty-one patients (26SW/15SV) received glucocorticoid (GC) replacement therapy to achieve normal androgen levels. Obesity was defined by BMI≥95th percentile. NR3C1 alleles were genotyped, and association analyses with phenotype were done with Chi-square, t-test, and multivariate and regression analysis. Results. Obesity was observed in 31.7% of patients and was not correlated with GC doses and treatment duration. Z-score BMI was positively correlated with blood pressure, triglycerides, LDL-c levels, and HOMA-IR. NR3C1 polymorphisms, BclI and A3669G, were found in 23.1% and 9.7% of alleles, respectively. A3669G carriers presented higher LDL-c levels compared to wild-type subjects. BclI-carriers and noncarriers did not differ. Conclusion. Our results suggest that A3669G-polymorphism could be involved with a susceptibility to adverse lipid profile in pediatric CAH patients. This study provides new insight into the GR screening during CAH treatment, which could help to identify the subgroup of at-risk patients who would most benefit from preventive therapeutic action.